Optimizing Generator Power Usage Through LED Lighting Distribution on Tugboats: A Case Study of a 26.80-Meter Vessel - Suardi, Suardi; Pratama, Brian Yoga; Pawara, M Uswah; Yosefan, Andreyano; Anugerah, Andi Nurwahid; Abdurrahman, Luthfi; Tasrief, Muhdar; Klara, Syerly (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
The 26.80 meter long tugboat plays a critical role in Indonesia’s maritime operations, particularly in towing and maneuvering vessels between Semayang Port and open sea areas. As part of its operational infrastructure, the vessel relies on fluorescent lighting systems, which are known to be less energy efficient and less durable than modern lighting technologies. This presents a significant operational challenge, particularly in light of rising fuel costs and the global shift toward more sustainable maritime practices. This study addresses the issue of inefficient energy use in onboard lighting systems by evaluating the performance of conventional fluorescent lamps compared to Light Emitting Diode (LED) lighting on tugboats. The objective is to assess and compare both lighting types in terms of energy consumption, lighting uniformity, and compliance with international lighting standards set by classification societies. The research adopts the Zonal Cavity Method (ZCM), which involves dividing the interior of the tugboat into three lighting analysis zones: the High-Ceiling Cavity (HCC), High-Rise Cavity (HRC), and High-Floor Cavity (HFC). Each zone was analyzed to determine the required illumination levels based on standardized guidelines, enabling a systematic comparison of lighting performance between the two technologies. Results indicate that LED lighting systems outperform fluorescent lighting in all evaluated aspects. LEDs provided significantly higher energy efficiency and more uniform lighting distribution across all zones of the tugboat. Additionally, LED systems demonstrated better compliance with minimum illumination levels as outlined in international maritime lighting standards. The study concludes that implementing LED lighting can lead to substantial improvements in shipboard energy efficiency, reduced generator load, lower operational costs, and improved environmental sustainability. These findings suggest that maritime operators should consider transitioning to LED systems as a long-term solution for enhancing energy performance. Future research is recommended to explore the integration of LED systems with renewable power sources such as solar energy, and to evaluate the long-term economic and maintenance benefits across different vessel types and operational profiles.